2021
DOI: 10.3390/jcm10092029
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hamstring Injury Prevention Programs in Eleven-a-Side Football Players Based on Physical Exercises: Systematic Review

Abstract: (1) Objective: To analyze the exercise programs used to prevent of acute hamstring injuries in eleven-a-side football players, and their effectiveness. (2) Methods: A systematic review (PRISMA) was conducted (2008–2020), including RCTs, that exclusively used physical exercises as a prevention method. (3) Results: Ten studies were selected considering 14 interventions, including nine different programs: FIFA11+ (11+), Harmoknee, eccentric Nordic Hamstring Exercise (NHE) exclusively, with eccentric exercises, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The characteristics of the eight eligible articles included in the umbrella review can be found in Table 2 (Ref. [3,[17][18][19][35][36][37][38]). The summary of the main evidence found in each review article is outlined in Table 3 (Ref.…”
Section: Characteristics Of the Study And Qualitative Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…The characteristics of the eight eligible articles included in the umbrella review can be found in Table 2 (Ref. [3,[17][18][19][35][36][37][38]). The summary of the main evidence found in each review article is outlined in Table 3 (Ref.…”
Section: Characteristics Of the Study And Qualitative Synthesismentioning
confidence: 99%
“…The summary of the main evidence found in each review article is outlined in Table 3 (Ref. [3,[17][18][19][35][36][37][38]). There were 60 articles included in the eight systematic reviews, with 20 being repeated, two of which included female soccer players [39,40], two focused on injury prediction [41,42], one with a mixed sample [43], three systematic reviews, of which one was already within this review [18], another was mixed [44] and the last jointly involved risk factors, detection and prevention tests with articles that were already included in the other reviews [45], five of optimisation [46][47][48][49][50], one developed in Australian soccer [51] and one not available [52].…”
Section: Characteristics Of the Study And Qualitative Synthesismentioning
confidence: 99%
See 3 more Smart Citations